2012
DOI: 10.1021/nl204283q
|View full text |Cite
|
Sign up to set email alerts
|

A Stable “Flat″ Form of Two-Dimensional Crystals: Could Graphene, Silicene, Germanene Be Minigap Semiconductors?

Abstract: The discovery of a flat two-dimensional crystal known as graphene has contradicted Landau-Peierls-Mermin-Wagner arguments that there is no stable flat form of such crystals. Here, we show that the "flat" shape of graphene arises due to a microscopic buckling at the smallest possible interatomic scale. We show that the graphene, silicene, and other two-dimensional crystals are stable due to transverse short-range displacements of appropriate atoms. The distortions are small and form various patterns, which we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
202
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(209 citation statements)
references
References 34 publications
(56 reference statements)
7
202
0
Order By: Relevance
“…Graphene not only has a linear electronic energy spectrum but may also have a very high mobility of charge carriers even when impurities are present [21]. Recently, the formation of a highly inhomogeneous network of graphene in a graphite sample was observed due to a buckling effect [22,23]. Such inhomogeneous structures may exhibit a large EMR effect [24].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene not only has a linear electronic energy spectrum but may also have a very high mobility of charge carriers even when impurities are present [21]. Recently, the formation of a highly inhomogeneous network of graphene in a graphite sample was observed due to a buckling effect [22,23]. Such inhomogeneous structures may exhibit a large EMR effect [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, single-layer thick sp 2 and sp 3 group IV systems have attracted considerable theoretical and experimental interest. [14][15][16][17] It has been previously shown that layered Zintl phases such as CaSi2 and CaGe2 can be topochemically deintercalated in aqueous HCl at low temperatures to produce layered silicon and germanium solids. [18][19][20] The resultant four-coordinate puckered lattice of Si and Ge atoms has an analogous geometry to sp 3 -hybridized graphane, or a Si/Ge(111) surface in which every Si/Ge atom is terminated with either -H or -OH above or below the layer.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] A wide range of 2D materials [6][7][8][9] has been developed since the discovery of the prototypical 2D material, the graphene. 10 These materials may find applications in flexible electronics, 11 high frequency electronics, 12 photo detectors, [13][14][15] and many other electronic and photonic applications.…”
Section: Introductionmentioning
confidence: 99%